Cellular communication via nanoparticle-transporting biovesicles. (April 2014) - Ferrati, Silvia; McConnell, Kellie I; Mack, Aaron C; Sirisaengtaksin, Natalie; Diaz, Rodrigo; Bean, Andrew J; Ferrari, Mauro; Serda, Rita E
Aims: Endothelial cells are dynamic cells tasked with selective transport of cargo from blood vessels to tissues. Here we demonstrate the potential for nanoparticle transport across endothelial cells in membrane-bound vesicles.Materials & methods: Cell-free endothelial-derived biovesicles were characterized for cellular and nanoparticle content by electron microscopy. Confocal microscopy was used to evaluate biovesicles for organelle-specific proteins, and to monitor biovesicle engulfment by naive cells.Results: Nanoparticle-laden biovesicles containing low-density polyethyleneimine nanoparticles appear to be predominately of endosomal origin, combining features of multivesicular bodies, lysosomes and autophagosomes. Conversely, high-density polyethyleneimine nanoparticles stimulate the formation of biovesicles associated with cellular apoptotic breakdown. Secreted LAMP-1-positive biovesicles are internalized by recipient cells, either of the same origin or of novel phenotype.Conclusion: Cellular biovesicles, rich in cellular signals, present an important mode of cell-to-cell communication either locally or through broadcasting of biological messages. Original submitted 30 August 2012; Revised submitted 2 February 2013